HIV-1-derived single-stranded RNA acts as activator of human neutrophils (2016)
Neutrophils are key effector cells of the innate immune system and are involved in the host defense against invading pathogens such as viruses. Recently, it was reported that HIV-1-neutrophil interaction triggers neutrophil activation and promotes expression of Toll-like receptors (TLR). Here, we assessed the role of single-stranded RNA40 (ssRNA40) derived from HIV-1 in neutrophil activation. We observed functional activation of neutrophils in response to HIV-1-derived ssRNA40 based on the expression of TLR7/8, RIG-I and MDA5, induction of cytokines (IL-6 and TNF-α) and the production of reactive oxygen species (ROS). Additionally, ssRNA40 promoted the expression of CD62L and TNF-α and the production of ROS in the presence of the TLR2 agonist Pam2CSK4. ssRNA40 together with R848 (an RIG-I/MDA5 agonist) increased CD11b expression but decreased CD62L expression. Furthermore, decreased IL-6 expression was observed in the presence of the TLR4 agonist LPS. Finally, we found that ssRNA40 promotes RIG-I and MDA5 expression in the presence of the TLR2, TLR4 and TLR7/8 agonists. This study demonstrates a functional response of TLRs in neutrophils challenged with ssRNA40, suggesting that TLRs could be involved in the innate immune response observed during HIV infection, which might be mediated by its genome.